Dust deposition and cleaning effect on PV panel: Experimental approach - Hussain Saad Abd; Hadia Kadhim Judran; Salah H. Abid Aun; Ameer Abed Jaddoa; Karrar A. Hammoodi; Saif Ali Kadhim; Jafaar Mohammed Daif (Results in Engineering, 2025)
This study looked at how dust particles affect the performance of photovoltaic (PV) solar panels, specifically how they lower their efficiency and power output. From March 15 to May 15, 2024, experiments were carried out at the University of Technology in Baghdad. The results showed that dust density has a major impact on PV panels' power output, open-circuit voltage (Voc), and short-circuit current (Isc). The power output was observed to decrease by 34 % at a dust level of 10 g/m². Additionally, there was a significant nonlinear correlation found between the fill factor (FF), dust density, and conversion efficiency. The PV conversion efficiency experienced a notable drop, decreasing from 19.8 % to 6.3 % over three months at a constant irradiance of 750 W/m². Also, the results show that the PV conversion efficiency is constant at a particular particle density, with a nonlinear relationship between particulate density and conversion efficiency. Finally, dust deposition reduces solar PV panel efficiency by 7.8 %–19.2 %. This experiment showed 6.8 %–7.9 % effectiveness improvement. Interestingly, wind and rain were found to have a positive effect on solar PV panels by removing accumulated dust, thereby enhancing their performance. These results emphasize the importance of developing effective cleaning strategies to optimize the efficiency of PV panels, particularly in regions like Iraq, where high dust levels and extreme temperatures prevail.